A Scheme of Quantum Tunnel Field Effect Transistor Based on Armchair Graphene Nano-Ribbon. (17th September 2021) - Vali, Mehran; Moezi, Negin; Heidari, Hadi; Bayani, Amirhossein
Abstract : We proposed a scheme of armchair graphene nanoribbon (AGNR) based tunnel field-effect transistor (TFET). The simulated device consists of two (AGNR) electrodes with zigzag termination that are separated by a narrow gap. The Fermi level of two electrodes is controlled with a common back gate. The main idea is based on taking advantage of the electronic effects of smooth edge atoms of (AGNR) and investigating the effect of applied small uniaxial tensile strain and gate voltage on the output characteristics of simulated TFET. Our analysis shows that the simulated device will have a pronounced negative differential conductance high peak to valley ratio at room temperature. We see that by applying the uniaxial tensile strain, this ratio upgrades to 70 for (AGNR) with width N = 13.